Prolonged Biologically Active Colonic Tissue Levels of Curcumin Achieved After Oral Administration—A Clinical Pilot Study Including Assessment of Patient Acceptability - Glen R.B. Irving; Lynne Howells; Stewart Sale; Ines Kralj‐Hans; Wendy Atkin; Susan K. Clark; Robert G. Britton; Donald J. L. Jones; Edwina N. Scott; David P. Berry; David Hemingway; A. S. Miller; et al. (2012)
Abstract Curcumin, the main constituent of turmeric, is suspected to possess cancer chemopreventive properties. Pharmacokinetic and pharmacodynamic parameters have been reported, but few data exist describing whether methodologies are suitably robust for curcuminoid detection in colonic biopsy specimens. Information on the acceptability of prolonged administration of daily curcumin is not available. This is of vital importance to implement chemoprevention strategies. This study aimed to quantify levels of curcuminoids in colorectal mucosa of patients undergoing colorectal endoscopy or surgical resection and to obtain information on the acceptability and compliance with daily curcumin. Curcumin C3 complex (2.35 g) was administered to patients once daily for 14 days before endoscopic biopsy or colonic resection. Safety and tolerance were monitored. Analysis of curcuminoids in plasma, urine, and colonic mucosa was conducted by ultraperformance liquid chromatography (UPLC)-UV with characterization by liquid chromatography/tandem mass spectrometry (LC/MS-MS). Twenty-four of 26 patients commencing curcumin completed the course. Six patients reported mild gastrointestinal adverse events. Curcuminoids were detectable in nine of 24 plasma samples, 24 of 24 urine samples, and in the colonic mucosa of all 23 biopsied participants. Mean tissue levels were 48.4 μg/g (127.8 nmol/g) of parent curcuminoids. The major conjugate, curcumin glucuronide, was detectable in 29 of 35 biopsies. High levels of topical curcumin persisted in the mucosa for up to 40 hours postadministration. Sixteen participants (67%) stated that they would take curcumin long-term should it be of proven benefit. In summary, pharmacologically active levels of curcumin were recovered from colonic mucosa. The regimen used here seems safe, and patients support its use in long-term trials. Cancer Prev Res; 6(2); 119–28. ©2012 AACR.